The effects of milling and cooking on the total phenolic content and DPPH radical scavenging activity of white heirloom Rice (Oryza sativa) varieties - Calub, Marcela Simone C.; Cornago, Djanna F. (Quezon City College of Home Economics, University of the Philippines Dilman, 2015)
In this study, the effects of polishing and cooking on the total phenolic content (TPC) = and 1, 1-Diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity of different white rice varieties (three heirloom rice varieties: Tinawon Inbangul, Tinawon Innawi, and Manteka; two controls: Basmati and Jasmine) were evaluated and correlated to grain size, grain weight, moisture content, and grain color. TPC and DPPH radical scavenging activity followed the trend Basmati>Manteka>Tinawon Innawi> Tinawon Inbangul>Jasmine. Dehulled rice had the greatest TPC and DPPH radical scavenging sctivity. TPC was measured to be 30.11-53.25, 18.94-38.83, and 23.85-32.31 mg GAE/100g for dehulled, polished, and cooked rice respectively. Polishing had significantly greater (p<0.05) effect on TPC than cooking for most of the cultivars, except Manteka and Basmati. DPPH radicalscavenging activity expressed as EC50 values were 213.12-278.82, 284.99-525.93, and 330.64-474.64 g/L for dehulled, polished, and cooked rice respectively. Most samples exhibited no significant difference (p>0.05) in terms of reduction of radical scavenging activity of polished versus cooked rice with the exception of Manteka and Jasmine. Reduction of TPC and radical scavenging activity values are due to the reduction of antioxidant-rich bran layer and decomposition and leaching of soluble phenols. A high correlation of TPC to DPPH radical scavenging activity (r = -0.900, p<0.01) was observed indicating that phenolics may be responsible for the scavenging activity. TPC and DPPH radical scavenging activity were also highly correlated (p<0.01) to color. These results can be used to help rice farmers select breeding lines high in antioxidants on the basis of color. To further improve the study, assessment of bound phenolics and proper handling of fresh samples are recommended.
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Keywords: Rice -- Philippines; Rice -- Varieties -- Philippines